Type 1 Ig-E mediated allergy to human insulin, insulin analogues and beta-lactam antibiotics Hipersensibilidade imediata a insulina humana, análogos de insulina e a antibióticos beta-lactâmicos - Pedro Andrade; Luísa Barros; Margarida Gonçalo (Sociedade Brasileira de Dermatologia, 2012)
Insulin, a crucial therapeutic agent for diabetes mellitus, has been rarely associated with hypersensitivity events. We present a 69-year-old type-2 diabetic patient with urticariform lesions on the sites of subcutaneous injection of insulin. The patient denied any known allergies, except for an unspecific cutaneous reaction after intramuscular penicillin administration in childhood. Prick tests revealed positive reactions to all tested human insulins and insulin analogues. Serum IgE levels were above normal range and RAST tests were positive for human, bovine and porcine insulins, as well as beta-lactams. Type 1 IgEmediated allergy to insulin analogues demands a prompt diagnosis and represents a significant therapeutic challenge in diabetic patients. A insulina é um agente indispensável para o controlo da diabetes mellitus. Os efeitos adversos da sua administração, em particular fenómenos de hipersensibilidade, são raros. Apresentamos um doente de 69 anos, diabético do tipo 2, com episódios recorrentes de lesões urticariformes nos locais de administração subcutânea de insulina. Negava alergias medicamentosas, à excepção de reacção não especificada na infância após penicilina intramuscular. Foram realizados testes cutâneos por puntura (prick tests) com diversos tipos de insulina humana e análogos, todos com reacções positivas, associando elevação dos níveis de IgE sérica e provas RAST positivas para as insulinas humana, bovina e porcina e para os antibióticos beta-lactâmicos. A alergia a análogos de insulina exige um diagnóstico precoce, originando um desafio terapêutico importante no doente diabético.